[2]Paracyclo[2](2,5)pyridinophan - J. Bruhin; W. Jenny (CHIMIA)
The synthesis of [2]paracyclo [2](2,5)pyridinophane by a “cross-breeding” Hofmann-1,6-elimination reaction from a mixture of 4-methyl-benzyl-trimethylammonium hydroxide and 5-methyl-picolinyl(2)-trimethylammonium hydroxide is described. The 1H-NMR spectrum of [2]paracyclo [2](2,5)-pyridinophane shows for the benzene ring remarkable pseudo-geminal and pseudo-ortho downfield shifts caused by transannular influence of the pyridine N-atom.